Pemberdayaan Industri Kreatif Sektor Kerajinan di Sumatera Barat melalui Entrepreneurial Marketing; Studi pada UMKM Bordir dan Sulama - Yeni, Yulia Hendri; Luthan, Elvira; Hastini, Lasti Yossi; Primasari, Anggita (Universitas Brawijaya, Indonesia, 2014)
At West Sumatra, there are so many corporation in micro scale, small, and average (UMKM).There are common crafting industries which are driven by three prior elements such as creativity, innovation, and business. Embroidering is an icon of West Sumatra and it contributes toward economic. Based on the previous research, it could be seen that the capability of the businessman in managing corporation is limited. In addition, the government noted that this case is a prior National strategic issue related to the managerial competence need from the businessman, especially Entrepreneurship and Marketing. Both of managerial aspects are known as Entrepreneurial Marketing. The aim of the research is to empower embroider crafting of UMKM through Entrepreneurial Marketing. In addition,this research want to give an image concerning to the relationship between Entrepreneurial Orientation, Market Orientation, and organization performance. This research used quantitative approach by conducting questionnaire. The analysis conducted by using Structural Equation Modeling.